Cancer symptom scale preferences: does one size fit all?. Issue 2 (10th August 2016) - Jeter, Kirby; Blackwell, Siobhan; Burke, Lucy; Joyce, David; Moran, Catherine; Conway, Emma Victoria; Cremen, Iseult; O'Connor, Brenda; Ui Dhuibhir, Pauline; Walsh, Declan
Abstract : Objectives: Patients with advanced cancer do not report all symptoms, so assessment is best done systematically. However, for such patients, completion rates of some symptom instruments are <50%. Symptoms can be quantified by various scales including the Categorical Response Scale (CRS), Numerical Rating Scale (NRS) and Visual Analogue Scale (VAS). Patient preferences for CRS, NRS and VAS in symptom assessment and their clinical utility in 3 cancer symptoms: pain, tiredness and appetite loss were determined. Methods: A prospective survey was conducted involving cancer admissions to a 36-bed palliative care unit. Results: 100 inpatients were recruited, aged 38–93 years (x̅ =71 years; SD=11.6), with median Eastern Cooperative Oncology Group (ECOG) scores of 2 (range 0–4). VAS was the least preferred measure. 52% of patients choose the same scale for all 3 symptoms and 44% for 2, with 4% choosing a different individual scale per symptom. There was moderate agreement between participant scale preference and observer determined ease of scale completion (loss of appetite: κ=0.36; pain: κ=0.49; tiredness: κ=0.45). Participants preferred CRS for appetite loss (48%) and tiredness (40%) and NRS for pain (44%). Conclusions: VAS was the least favoured scale and should be used cautiously in this population. Most participants had a scale preference with high intrapatient consistency between scales. CRS was preferred for appetite loss and tiredness and NRS for pain. Consideration should be given to individualised cancer symptom assessment according to patient scale preference.